2016
DOI: 10.1002/asl.691
|View full text |Cite
|
Sign up to set email alerts
|

Changes in marine fog in a warmer climate

Abstract: Changes in marine fog in a warmer climate are investigated through simulations using the atmospheric component of a global climate model, with both observed and perturbed sea surface temperature forcing. Global changes in marine fog occurrence in different seasons are compared. We show that the changes in marine fog occurrence correspond well to changes in horizontal temperature advection near the surface in a warmer climate. Therefore, the changes in marine fog can be well explained by large-scale circulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Results from the CMIP5 experiments were open to climate research communities, leading to many studies that evaluated various aspects of model performance and contributed to the understanding of the climate system. MRI-CGCM3 has also been used for a broad range of studies such as climate change, paleoclimate, and climate extreme events (e.g., Kawai et al 2016;Kaiho et al 2016; Kaiho and Oshima 2017). The sixth phase of the CMIP (CMIP6), which is expected to fundamentally contribute to the Intergovernmental Panel on Climate Change's Sixth Assessment Report, has been planned (Eyring et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Results from the CMIP5 experiments were open to climate research communities, leading to many studies that evaluated various aspects of model performance and contributed to the understanding of the climate system. MRI-CGCM3 has also been used for a broad range of studies such as climate change, paleoclimate, and climate extreme events (e.g., Kawai et al 2016;Kaiho et al 2016; Kaiho and Oshima 2017). The sixth phase of the CMIP (CMIP6), which is expected to fundamentally contribute to the Intergovernmental Panel on Climate Change's Sixth Assessment Report, has been planned (Eyring et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is again underscored by more recent studies (e.g., Wu et al, 2007). Noting that under the projected future warming the in-cloud liquid water content of marine fogs is projected to increase (Kawai et al, 2016), a higher risk of ship collisions can be reasonably inferred. Qu et al (2015) maintain that climate change is at least partly responsible for the observed steady decrease in winter visibility over eastern China.…”
Section: Risk I7: Increased Load On Bridges With Control Sluice Gatesmentioning
confidence: 99%
“…Marine fog [1] reduces visibility to less than 1 km and is responsible for 32% of worldwide sea accidents [2]. Regarding global warming [3], changes in marine fog occurrence correspond well with horizontal temperature advection changes near the surface in numerical simulations, including the Southern Ocean around Antarctica [4]. Fog and mist over polar seas are highest in the summer and are rarely observed during winter [5], and the process of their onset, maintenance, and disappearance are all closely related to interactions between the atmosphere, sea, land, and ice.…”
Section: Introductionmentioning
confidence: 99%
“…Khwairakpam et al investigated an episode of coastal advection fog over East Antarctica oases recorded by monostatic acoustic sodar, and they showed that this type of fog was an important source of water for microbes [32]. Overall, marine fog processes in the Antarctic region are largely unknown [4,5]. The aim of this paper is to elucidate the development of King George Island marine fog through site observations and to highlight the dominant processes of its formation in the area.…”
Section: Introductionmentioning
confidence: 99%